THE POSITION OF TABUNG HAJI UNDER BANK NEGARA MALAYSIA: ISSUES AND CHALLENGES (SALAM Digest: Syariah and Law Undergraduate Symposium, 2023)
This article delves into the critical role of Lembaga Tabung Haji (TH) in Malaysia, a pivotal entity dedicated to managing the welfare and financial aspects of Malaysian Muslims undertaking the Hajj pilgrimage. It scrutinizes the unique relationship between TH and Bank Negara Malaysia (BNM), the overarching authority overseeing Islamic financial institutions (IFIs) in Malaysia, with a focus on ensuring Shariah compliance. The study becomes particularly relevant considering the 2018 crisis, where TH's governance was temporarily placed under BNM's oversight, raising questions about the institution's autonomy and regulatory framework. The research adopts a qualitative methodology, drawing on a diverse array of primary and secondary sources, to offer a comprehensive overview of the legislative and jurisdictional landscapes governing both TH and BNM. Key legislations, such as the Tabung Haji Act 1995 for TH and the Central Bank of Malaysia Act 2009 (CBMA 2009) and Islamic Financial Services Act 2013 (IFSA 2013) for BNM, are analyzed to understand their implications on the operations of these entities. A crucial aspect of this study is the exploration of the current challenges and issues confronting TH, particularly in the context of its governance and the potential impact of BNM’s supervision. The findings reveal that while TH operates as a specialized Islamic institution under its own act, BNM serves as the regulatory body for all IFIs in Malaysia. The study further highlights the importance of Hajj, accessible only to those who are financially and physically capable, and notes the financial assistance provided to individuals from the B40 and M40 income groups for the pilgrimage. The article concludes with a critical analysis of the implications of TH's governance under BNM's oversight. It argues that such a shift could lead to political interference in TH's administration and a potential deviation from its foundational purpose – serving the Muslim community's Hajj-related needs – towards becoming a more generalized IFI accessible to all, including non-Muslims. This possibility raises significant concerns about the future direction and integrity of TH as a religious and financial institution.